ANALISIS KANDUNGAN UNSUR HARA PADA KOTORAN SAPI DI DAERAH DATARAN TINGGI DAN DATARAN RENDAH - Linus Melsasail; Verry R.Ch. Warouw; Yani E.B Kamag (COCOS, 2018)
ABSTRACT Agricultural development, basically aims to increase production towards self-sufficiency, To achieve these objectives, it is necessary to have innovations to increase agricultural production. One of the main things that supports agricultural productivity is nutrients. This research uses survey method and laboratory analysis. Livestock manure samples were taken at 2 points, namely in the highlands and lowlands. Each point is taken one sample. Observation variables consisted of pH, Nitrogen, Phosphorus, Potassium, C-organic. The results showed some nutrient content from cow dung at the observation site, namely the nutrient content of C-Organic, the highest was at the location in Tomohon 1, amounting to 10.42%, while the lowest C-Organic value was at the location in the Kalasey Village of 8 69%. For nitrogen element (N-total), the highest value is obtained from cow dung in the lowlands (Kalasey) which is 0.88% while the lowest N-Total value is obtained in the Tomohon area which is 0.68%. For phosphorus (P-total), the highest value obtained from Tomohon land is 0.34% with moderate criteria. While the lowest P-total value was obtained from the Kalasey field, which was 0.22% (low). The highest potassium (K2O) was obtained from cow dung in the lowlands (Kalasey 1), which was 0.56%. While the lowest K2O value was obtained from the land in Tomohon which was 0.36%. In addition, the Tomohon plateau area has high water content because the land is a former paddy field area. Keywords: Nutrient, Cow dung, organic fertilizer